Racjonalność a wiara w Boga - Spaemann, Robert (Poznańskie Studia Teologiczne, 2009)
Starting with his own modification of Plato’s allegory of the cave the author explains the notion of creation, which does not mean a single initiating event but the grounding of the entire process of the world in a creative will that lies outside of this process. Faith in God is faith in a reason for the world, which is not itself groundless, as the scientific worldview holds. When we think the concept „God”, we think the unity of two predicates that are only occasionally and never necessarily bound together in our earthly experience of the world: the unity of absolute power and absolute goodness, i.e. the unity of being and meaning. After Nietzsche we can no longer rest the proofs for the existence of God on the human capacity for truth, for its foundation is sure only if we presuppose the existence of God. However, there is a grammar based proof that is Nietzscheresistant. The rationale of the futurum exactum, the future perfect tense, shows that the reality of the present entails the reality of the past. The question is: What sort of reality does the past have? The sole answer can be: We have to think of a consciousness in which everything that happens is taken up, an absolute consciousness.